Electrochemically active bacteria sense electrode potentials for regulating catabolic pathways - Atsumi Hirose (Nature Portfolio, 2018)
Whether electrochemically active bacteria (EAB) can gain energy according to electrode potentials is still unclear. Here, the authors show through transcriptome and deletion mutant analyses that EAB can sense electrode potentials by the Arc system and activate NADH-dependent catabolic pathway to generate ATP.